Analisis Perbandingan Data Optical Distribution Point di Lapangan dengan Data Sistem (Unified Inventory Management) di Unit Access Optima Data & Maintenance PT. Telkom Indonesia Witel Karawang - Azmy Wahyudi; Dian Budhi Santoso (Peneliti.net, 2023)
This article is created to explain the Comparative Analysis of Optical Data Distribution Points in the Field with Data Systems (Unified Inventory Management) in the Optima Data & Maintenance Access Unit of PT. Telkom Indonesia Witel Karawang. The purpose of this study is to find out which ports have been used at the Optical Data Distribution Point, and the layout of the Data Optical Distribution Point also makes it easier for the public to see the distribution path at the Data Optical Distribution Point, and helps check whether there is damage to the existing ports at the Data Optical Distribution Point. The research was conducted using interview, literature, and observation methods. This research uses the website tools System Data (Unified Inventory Management) and Valins PT. Telkom Witel Karawang to assist in analyzing Optical Distribution Point Data.